ANALYSIS OF DEFECT OUTSIDE DIAMETER (+) MOVEABLE SPRING TYPE DRIVEN USING THE SEVENTOOLS METHOD - Pradana, Hafidz Lingga Allen; Andesta, Deny (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
PT. ISP is a manufacturing company that focuses on the production of springs for vehicles in the industrial sector. The products produced include leaf springs and snail springs, which are produced via cold and hot processing methods. PT. ISP collaborates with Mitsubishi Steel Manufacturing, Japan, using a license from that company. One of them is Moveable Driven, which is a type of spiral spring that is produced through a cold process. PT. ISPs face challenges related to defects that arise during the production process. This research aims to assess the level of defects, identify factors that contribute to product defects and suggest improvements. Seventools method for identifying factors that cause defects in products. The research results based on the Pareto diagram show that the most dominant type of defect is Outside Diameter (+) with a total of 3,197 pcs with a percentage of 44.9%, so defects need to be the main focus for improvement. On the P Chart, there is 1 data that is out of control below the Lower Control Limit/LCL limit in the 9th data. After revision 1 there is no data out of control. In this way, the factors causing Outside Diameter (+) defects using fishbone include Man Factor, Measurement Factor, Machine Factor, Process Capability, Method Factor. The condition of internal defects is still within control limits. So improvements need to be made so that defects meet the targets that have been set.